Delayed-onset sinus node dysfunction in a child victim of Russell's viper bite. (May 2020) - Athapathu, Arjuna Salinda; Arunath, Visvalingam; Aruppala, Aruppala AHS; Hoole, Thabitha Jebaseeli; Suntharesan, Kanagapathasuntharam; Mettananda, Sachith
Cardiac complications following envenomation by Russell's viper venom are uncommon. We describe a 14-year-old girl who developed delayed-onset sinus node dysfunction. She presented with mucosal bleeding, ptosis, and muscle weakness. Her 20-min whole blood clotting time and international normalized ratio were prolonged. The initial electrocardiogram showed sinus tachycardia. Her systemic manifestations responded to antivenom serum. After 24 h, she developed bradycardia and electrocardiography showed sinus node dysfunction with sinus arrest and an atrial escape rhythm. This case shows that arrhythmias can have a delayed onset even after resolution of other systemic manifestations, and even after treatment with antivenom serum.